LANGUAGE AND GENDER ON SOCIAL MEDIA: A CRITICAL DISCOURSE ANALYSIS OF TIKTOK COMMENTS - Zainuddin; Karim (JALC : JOURNAL OF APPLIED LINGUISTIC AND STUDIES OF CULTURAL, 2025)
This study investigates the interplay between language and gender on social media, focusing on user comments on TikTok. By employing Critical Discourse Analysis (CDA), the research aims to uncover how gender ideologies are constructed, reinforced, or challenged in digital discourse. A total of 500 comments were collected and analyzed qualitatively to identify dominant linguistic patterns and gendered discursive strategies. The findings reveal that while many users reproduce traditional gender norms—such as objectification of women and stereotyping of men—others engage in discursive resistance by promoting inclusivity and challenging dominant narratives. The study also highlights how humor, sarcasm, and multimodal expressions (emojis, non-standard spellings) play a central role in shaping and performing gender online. The research concludes that TikTok functions as a contested space where power, identity, and ideology intersect through language. These findings underscore the importance of analyzing everyday digital communication to better understand contemporary gender discourse.